Assessing subsidy integration in the 40 years of agricultural planning in the Maldives - Mohamed, Ilham Atho (Frontiers in Sustainable Food Systems, 2024)
87% of agricultural subsidies are harmful to the environment and human health while contributing little to food security. As seen in the case of climate change, small island states are the most vulnerable to the impacts of environmental degradation resulting from activities they have little contribution towards. When it comes to subsidies, the relative contribution to the impacts of subsidies by islands, as well as the relative impacts of subsidies on islands, is not studied. There is a dearth of research on agricultural subsidies in Small Island Developing States (SIDS) such as the Maldives, leaving a void in this global knowledge pool. Literature shows that the first step to addressing subsidies is to identify and trace them in policies. To contribute towards bridging the knowledge gap on understanding the status of subsidies in islands, this study identified and assessed the historical trends of subsidy integration in Maldivian agricultural policy by analyzing their temporal distribution patterns and the quality of subsidy inclusion in national planning for the past four decades. Using a classification of 15 subsidy types, the study adopted a scoring protocol to deliver a quantitative overview of the status and trends in subsidy in the agriculture sector of the Maldives. The results showed that although the scale of agriculture in the country is limited, subsidies have consistently been an integral part of agricultural planning since 1985, with agricultural inputs being one of the most frequently and highly subsidized over the years. Twelve different subsidy types were traced in the 10 assessed national plans, and eleven subsidy types were identified in the plan from 2019 to 2023. These results serve as a baseline for the understanding of subsidies in the Maldives by providing a narrative of an island state for the global overview of subsidies and for comparative studies thereof.